Direct Delamination of Graphene for High‐Performance Plastic Electronics. Issue 4 (17th September 2013) - Wang, Xiaohan; Tao, Li; Hao, Yufeng; Liu, Zhihong; Chou, Harry; Kholmanov, Iskandar; Chen, Shanshan; Tan, Cheng; Jayant, Nishant; Yu, Qingkai; Akinwande, Deji; Ruoff, Rodney S.
<x xml:space="preserve">Abstract</x> Electrochemical delamination is developed to transfer graphene for plastic electronics. The use of a sacrificial support during transfer is eliminated by depositing the target polyimide substrate directly onto graphene. A continuous and residue‐free graphene surface with less line disruptions (such as ripples and wrinkles) is obtained on the target polyimide substrate, and good mechanical durability as well as low sheet resistance is obtained. The properties are competitive with conventional transparent conducting films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>